2017
DOI: 10.1002/app.45696
|View full text |Cite
|
Sign up to set email alerts
|

Influence of adsorbed and nonadsorbed polymer additives on the viscosity of magnesium oxide suspensions

Abstract: Adsorbed polymer additives have been employed to reduce water content and improve cement workability through lowering viscosity, but the influence of over‐dosage and the presence of nonadsorbed chains have yet to be fully understood. Model magnesium oxide (MgO) suspensions were used to investigate the potential processing effect of “free” chain concentration on cementitious mixtures. The rheological impact of the free chains was measured through incorporation of nonadsorbing poly(ethylene glycol) (PEG) to susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…While the dispersant design has focused on the role of adsorbed polymer in mediating particle–particle interactions, the machine learning model that led to the design of LSPMAA incorporated solution forces in addition to particle forces . Indeed, experimental studies have demonstrated that intrinsic viscosity is important in determining the yield stress in concentrated suspensions, , suggesting that it needs to be considered as a design principle on par with effects on particle interactions.…”
Section: Resultsmentioning
confidence: 99%
“…While the dispersant design has focused on the role of adsorbed polymer in mediating particle–particle interactions, the machine learning model that led to the design of LSPMAA incorporated solution forces in addition to particle forces . Indeed, experimental studies have demonstrated that intrinsic viscosity is important in determining the yield stress in concentrated suspensions, , suggesting that it needs to be considered as a design principle on par with effects on particle interactions.…”
Section: Resultsmentioning
confidence: 99%
“…superplasticizers based on polycarboxylate-ether or naphthalene sulfonate, seem to work with MgO-based cements as well. However generally quite high dosages are needed for these cements e.g., MOC cement [120], MOS cement [121], MgO-based suspensions and paste [122][123][124], and MC cement [65]. Despite the high dosages, the retarding effect seems to be less than in the case of PC-based systems, and the addition of a retarder may still be necessary i.e.…”
Section: Admixturesmentioning
confidence: 99%
“…While there is theoretical support for this in models of polymer dispersants, there has been less work on the role of purely solution forces on workability, although experimental measurements on model systems indicate that this can be a strong determinant of suspension yield stress. [50] The introduction of metakaolin, which is believed to retain much of its intrinsic clay structure, lends further complexity due to its heterogeneous surface charge density and pH-dependent flocculation and adsorption behaviors. Addressing these issues may require parametrization of the system chemistry to resolve contributions from particle-particle interactions in the percolating network that comprises paste from solution-mediated effects due to changes in viscosity and polymer adsorption, [51] but this would provide a broader understanding of the forces that drive the rheological properties of MK-PC paste.…”
Section: Validationmentioning
confidence: 99%